Analisis Pengaruh Profitabilitas dan Kebijakan Dividen Terhadap Nilai Perusahaan dengan Struktur Modal sebagai Variabel Mediasi - Ready Wicaksono; Mispiyanti Mispiyanti (Politeknik Ganesha Medan, 2020)
This study aims to determine the relationship and influence of profitability variables, and dividend policy on firm value and capital structure variables as a mediator. The population is all state-owned companies listed on the Stock Exchange during 2015 - 2018. The sampling technique uses purposive sampling. Data analysis used regression and multiple tests. The results of this study prove that profitability has no effect on firm value but does affect the capital structure, dividend policy has an effect on firm value and also on capital structure, capital structure has no effect on firm value, the capital structure cannot mediate the relationship of profitability and dividend policy on firm value.